Measurement of the jet radius and transverse momentum dependence of inclusive jet suppression in lead-lead collisions at root S-NN=2.76 TeV with the ATLAS detector - Onofre, A. (2013)
Measurements of inclusive jet suppression in heavy ion collisions at the LHC provide direct sensitivity to the physics of jet quenching. In a sample of lead–lead collisions at √sNN = 2.76 TeV corresponding to an integrated luminosity of approximately 7 μb−1, ATLAS has measured jets with a calorimeter system over the pseudorapidity interval |η| < 2.1 and over the transverse momentum range 38 < pT < 210 GeV. Jets were reconstructed using the anti-kt algorithm with values for the distance parameter that determines the nominal jet radius of R = 0.2, 0.3, 0.4 and 0.5. The centrality dependence of the jet yield is characterized by the jet “central-to-peripheral ratio,” RCP. Jet production is found to be suppressed by approximately a factor of two in the 10% most central collisions relative to peripheral collisions. RCP varies smoothly with centrality as characterized by the number of participating nucleons. The observed suppression is only weakly dependent on jet radius and transverse momentum. These results provide the first direct measurement of inclusive jet suppression in heavy ion collisions and complement previous measurements of dijet transverse energy imbalance at the LHC.